Pragmatic Adaptive Trial for Respiratory Infection in Children (PATRIC) Clinical Registry protocol - Mark Jones; Meredith L Borland; Peter Richmond; Christopher C Blyth; Thomas L Snelling; Andrew C Martin; Rebecca Pavlos; Sarah Doyle; Sharon O'Brien; Mejbah U Bhuiyan; Daniel Oakes (BMJ Open)
Introduction Acute respiratory infections (ARI) are the most common cause of paediatric hospitalisation. There is an urgent need to address ongoing critical knowledge gaps in ARI management. The Pragmatic Adaptive Trial for Respiratory Infections in Children (PATRIC) Clinical Registry will evaluate current treatments and outcomes for ARI in a variety of paediatric patient groups. The registry will provide a platform and data to inform a number of PATRIC clinical trials, testing various interventions in ARI treatment and management to optimise paediatric ARI care.Methods and analysis The PATRIC Clinical Registry is a single-centre, prospective observational registry recruiting from a tertiary paediatric Emergency Department in Western Australia. Through characterising demographic, clinical, treatment and outcome data, the PATRIC Clinical Registry will improve our understanding of antibiotic utilisation and ARI outcomes in children.Ethics and dissemination The PATRIC Clinical Registry is conducted in accordance with the Declaration of Helsinki, and the International Council for Harmonisation (ICH) Guidelines for Good Clinical Practice (CPMP/ICH/13595) July 1996. Approval is provided by the Child and Adolescent Health Service Human Research Ethics Committee (HREC). Study results will be communicated by presentation and publication (HREC: RGS0000003078.)Trial registration number Australian New Zealand Clinical Trials Registry (ANZCTR): ACTRN12619000903189. UTN: U1111-1231-3365.